A friend for all seasons - Hubery, Julia (Atheneum Books for Young Readers, 2007)
Robbie the Raccoon and his friends love Father Oak and worry that he is sick when his leaves begin to turn color and fall off, but Robbie's mother explains what the change means and helps him plant some acorns as a sign of hope for spring.